A Study of Roof Caving in the Eastern U.S. Coalfields (International Conference on Ground Control in Mining, 1986)
Appropriate roof control is the most important requirement in underground coal mining and, in the case of longwall panels or second mining in room and pillar extractions, this can be simply expressed in terms of good and predictable roof caveability. Studies of roof caveability have been undertaken in many coalfields around the world. Most of their conclusions. however, are directly related to the mining and geological conditions experienced in these areas and as a result, may not be applicable to the conditions encountered in the Appalachian coalfield. Furthermore, some of these studies appear to be theoretical and conceptual, ignoring many important parameters of the geological environment, whereas others rely heavily on geological information but lack a rigorous foundations upon which quantitative design guidelines can be built. The objective of this study is to analyze caving and mass deformation characteristics above longwall panels in Appalachia and includes: - Analysis of the effects of the geological and geomechanical characteristics of the strata on the caving height and the bulking of the caved-material. - Testing of the applicability of the various theoretical and empirical models of roof caving. Formulation of a numerical around- deformation model for ion-elastic material behavior.